PENGARUH PENAMBAHAN TEPUNG DAUN SINGKIL (Premna Corymbosa) DALAM PAKAN IKAN TERHADAP PERTUMBUHAN LELE SANGKURIANG (Clarias Gariepinus Var. Sangkuriang) - Mabrurah, Muthmainah Qulub; Masitah, Masitah; Pribadi, Teguh; Nasution, Ruqoyyah; Rambitan, Vandalita (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
To maximize production, catfish farmers must optimize feed quality as one of the key factors supporting catfish growth and development. This study aimed to analyze the effect of adding singkil leaf flour (Premna corymbosa) to feed on the growth performance of Sangkuriang catfish (Clarias gariepinus var. Sangkuriang). The research was conducted from February to April using a randomized group design with four treatments and six replications. The treatments consisted of 100% pellets (P1), 100% singkil leaf flour (P2), 80% pellets + 20% singkil leaf flour (P3), and 70% pellets + 30% singkil leaf flour (P4). The analysis of singkil leaf flour showed a moisture content of 6.5%, ash content of 9.3%, protein 2.6%, fat 0.7%, and total carbohydrates 80.9%. The best growth performance was observed in the P3 treatment (80% pellets + 20% singkil leaf flour). It can therefore be concluded that singkil leaf flour alone cannot serve as an alternative single feed for catfish; however, it can be effectively used as a supplementary ingredient at a maximum proportion of 20% in combination with pellets.